2022
DOI: 10.3390/f13101663
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Soil Organic Carbon Fractions and Stability along a Chronosequence of Cryptomeria japonica var. sinensis Plantation in the Rainy Area of Western China

Abstract: Soil organic carbon (SOC) is critical for carbon cycling and sequestration in forest ecosystems. However, how stand age affects SOC components and stability still remains poorly understood. Here, soil samples (0–20 cm) were collected from Cryptomeria japonica var. sinensis (L. f.) D. Don plantations of seven stand ages (6, 12, 23, 27, 32, 46, 52 a) in the rainy area of western China. SOC fractions, including soil particulate organic carbon (POC), easily oxidizable carbon (EOC), labile organic carbon (LOC), rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported that LFOC is affected by organic matter input and decomposition rate [31]. The EOC is directly involved in the nutrient supply of plants and microorganisms, which is the most available component of SOC [32]. The results show that soil TN and POC were significantly positively correlated with LFOC and EOC, respectively (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have also reported that LFOC is affected by organic matter input and decomposition rate [31]. The EOC is directly involved in the nutrient supply of plants and microorganisms, which is the most available component of SOC [32]. The results show that soil TN and POC were significantly positively correlated with LFOC and EOC, respectively (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 57%
“…Our study found that soil readily oxidizable organic carbon content reached its maximum in the W0N32 treatment, and soil readily oxidizable organic carbon content is the main component of soil organic carbon. A higher ROC/SOC ratio indicates stronger soil organic carbon activity, while a lower ratio indicates more stable soil ( Han et al, 2022 ). Since soil readily oxidizable organic carbon content is mostly composed of recently fallen plant residues, nitrogen addition promotes the decomposition of surface litter by soil microbes, accelerating soil organic carbon turnover rates ( Liu F. et al, 2018 ; Liu H. Y. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in determining the nutrient regime of a specific soil and provides essential nutrients and substrates for soil microorganisms [ 9 ]. Soil scientists have described the labile fraction in various ways, including particulate organic carbon (POC) (53–2000 µm), light fraction organic carbon (LFOC) (density of < 2.0 g cm −2 ), readily oxidized carbon (ROC), soil microbial biomass carbon (SMBC), and dissolved organic carbon (DOC) [ 10 , 11 ]. The labile fraction primarily consists of mineral-free SOM composed of partially decomposed plant and animal residues that rapidly turn over and have a lower specific density compared to soil minerals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%